Quality assurance systems as a higher education policy tool in Korea: International convergence and local contexts. (November 2018) - Shin, Jung Cheol
Abstract: This study selected quality assurance systems in Korea as a case to analyze how global convergence and local contexts interplayed during three periods of change. Quality assurance is an example of a policy area where there was significant global convergence within a couple of decades. The quality assurance system in Korea was first adopted by the Ministry of Education in 1973. Since then, it experienced three major changes, in 1982, 1994, and 2008. This study has found that domestic contexts have been crucial in the adoption of quality assurance systems in Korea, though over time, growing similarities between Korean quality assurance and US models have become evident. In addition, policy convergence happens with modifications and these took place more or less depending on the prevailing local contexts. In Korea, the modifications in policy convergence responded to shortfalls in the existing quality assurance system rather than international pressure for quality assurance. Although over time there have been growing similarities at global level in quality assurance, the 'local prism' filters the external pressures.